Synergistic Effects of -cypermethrin and Dimethoate against Insect Pests (The East and Central African Journal of Pharmaceutical Sciences, 2018)
A series of mixture ratios of -cypermethrin and dimethoate insecticides were tested against several insects in the target range of each individual compound to establish the existence of synergism. The LC50 of each target insect was established and then used to evaluate the efficacy of the product. The two products when mixed in a ratio of 1:27 (-cypermethrin: dimethoate) were found to produce a synergistic effect.
Keywords: Synergism; pests; -cypermethrin; dimethoate